Assessing Middle School Students' Grasp of Definitions and Postulates in Euclid's Elements Volume I - Yulyanti Harisman; Cindy Eka Selvia; Hamdani Syaputra (Didaktik Matematika, 2025)
Euclid's Elements is a 13-volume textbook in mathematics and geometry written by the Greek mathematician Euclid in Alexandria, Egypt, in the early 3rd century B.C. and first published in 1482 AD in Europe. This book is a collection of definitions, postulates, theorems, and mathematical proofs of these propositions. This research aims to provide a glimpse of the history of Euclid's Elements and to determine the understanding level of junior high school students on the definition and postulates of Euclid's Elements. This research is qualitative research using literature review and case study methods. The case study was conducted on eight junior high school students, six female and two male. The instruments used in this research were analysis of several journals/articles and open interviews by asking several questions related to the definition and postulates of Euclid's Elements Volume I. The data analysis used in this research was meta-analytic and thematic. The results of this research provide information about the history of Euclid's Elements at a glance and the extent to which junior high school students know and understand the definitions and postulates contained in Euclid's Elements Volume I.